O Gabro coronítico de Amparo, RJ: petrografia, química mineral e geotermometria - Ludka, Isabel Pereira; Wiedemann, Cristina Maria (Anuário do Instituto de Geociências, 1997)
A gabbroic body of probable Brasiliano age, cropping out in a 4 km2 area around Amparo, in the state of Rio de Janeiro, was studied under the petrographic microscope and the electron microprobe. The dominant mineral assemblage consists of plagioclase (An 89<x<An98); olivine (Fo68<x<Fo73); amphibole (tschermakitic hornblende, Mg-hornblende and pargasite); OPX (En70<x<En76); spinel (pleonast); CPX (diopside); ilmenite, hematite, magnetite and sulphides. The uniformity of the mineral chemistry points toward a crystallization conditions in equillibrium with the parent magma. Important mineral reactions between olivine and plagioclase imply igneous reaction temperatures ranging from 850ºC to 900ºC